“Sou, sempre fui um estranho, um estrangeiro”: figurações do deslocamento em narrativas de Luiz Ruffato - Silva, Marcela Ferreira da (2019)
This doctoral thesis presents a reading of four narratives by contemporary Brazilian writer Luiz Ruffato, in order to observe how these texts have problematized the relation of the character to the space. Nowadays, through the incorporation of the theme of traffic within the great urban centers or through the innumerable developments of the migration inside and outside the country, the different figurations of the displacement are presented as a relevant problem in the fiction of the author. The choice of the corpus, which encompasses the major novels produced in just over a decade – Eles eram muitos cavalos (2001), O livro das impossibilidades (2008), Estive em Lisboa e lembrei de você (2009) and Flores artificiais (2014) –, sought to contemplate emblematic characters of this problematization subject and space: practitioners of urban space, migrants, immigrants and travelers respectively. The reading of the narratives made possible the reflection on the way in which the writer works the novel’s form to deal with the complexity of the uprooting and the belonging to a space. Each novel is structured in a unique way, requiring a theoreticalcritical analytical path of its own, which has observed both aesthetic and ideological issues. In general, the analysis allowed, from the perspective of space, that the many forms of migration, inserted in the novels, dialogue with a context of complex political configuration and that the multiplicity of tensions between displacement and belonging is one of the main concerns of the author’s aesthetic-ideological project.